Human leucocyte antigen‐Cw6 as a predictor for clinical response to ustekinumab, an interleukin‐12/23 blocker, in Chinese patients with psoriasis: a retrospective analysis. (15th October 2014) - Chiu, H.‐Y.; Wang, T.‐S.; Chan, C.‐C.; Cheng, Y.‐P.; Lin, S.‐J.; Tsai, T.‐F.
Summary: Background: Ustekinumab, an interleukin‐12/23 inhibitor, is effective in the treatment of psoriasis. A recent Italian study showed more favourable response to ustekinumab in patients with positive human leucocyte antigen (HLA)‐Cw6. Nonetheless, there are differences in genetic susceptibility to psoriasis between races, and no studies have specifically assessed the candidate genetic markers in predicting therapy outcome in Chinese patients with psoriasis treated with ustekinumab. Objectives: To determine whether HLA gene polymorphisms can predict the response to ustekinumab in Chinese patients with psoriasis. Methods: Sixty‐six patients with psoriasis treated with ustekinumab were included in the study, and the effectiveness of ustekinumab therapy was evaluated at weeks 0, 16 and 28 by Psoriasis Area and Severity Index (PASI). Results: More HLA‐Cw6‐positive patients achieved a PASI 75 response at week 4 compared with HLA‐Cw6‐negative patients (38% vs. 9%, P  = 0·019). Similarly, at week 16, patients carrying the HLA‐Cw6 allele showed a higher likelihood of achieving PASI 50, 75 and 90 than Cw6‐negative patients, although this was not statistically significant. At week 28, a significantly higher percentage of HLA‐Cw6‐positive patients maintained PASI 90 response compared with Cw6‐negative patients (63% vs. 26%, P  = 0·035). Further analysis of other HLA allele polymorphisms did not show significant associations with therapeutic response to ustekinumab. Conclusions: This pharmacogenetic study provides preliminary data indicating that positive HLA‐Cw6 is associated with a good response to ustekinumab treatment in Chinese patients with psoriasis. Abstract : What's already known about this topic? Biological therapies have revolutionized the treatment of psoriasis. Variability in genes involved in the immunological pathways of biological therapy may account for the different treatment outcomes. Human leucocyte antigen (HLA)‐Cw6 is the major psoriasis susceptibility gene and has a strong association with clinical psoriasis phenotypes. Studies investigating potential predictors for response to biologics are limited, particularly in Asian populations. What does this study add? Our study showed that HLA‐Cw6‐positive patients have a faster response and maintain a longer treatment response to ustekinumab than HLA‐Cw6‐negative patients. HLA‐Cw6 can be a pragmatic predictor for the response to ustekinumab not only in white patients but also in Chinese patients with psoriasis. These results will help dermatologists in guiding therapeutic decisions.